THE ANALYSIS OF FIGURATIVE LANGUAGE FOUND IN SONG LYRICS OF COLDPLAY'S ALBUM - Sani Kian Ramandani (JELLE, 2023)
Song is a beautified poem. It is one of the examples of literary work. Songgenerally contains figurative language. Figurative language are commonlyfound in song lyrics. For that reason, it brings the researcher of the thesis to analyze figurative language. In this research, the researcher analyzed kind of figurative language in song lyrics of Coldplay’s album. In this research, the writer used descriptive qualitative research and document analysis in order to answer the research problems in this study. This study is aimed to discuss the kind of figurative language that contains in song lyrics of Coldplay’s album. The Coldplay album consists seven songs. Those songs are A Message, Fix You, The Scientist, God Put a Smile Upon Your Face, Clocks, Parachutes, Yellow. After analyzing the data, the writer found six kinds of figurative language in song lyrics of Coldplay’s songs, those were hyperbole, simile, metaphor, personification, repetition, and onomatopoeia. This research is counted to find out the kind of figurative language in seven songs in Coldplay’s album. Keywords : Figurative language, song lyrics, coldplay’s album.